(untitled) (Experimental biology, 2015)
To prevent the negative impact of global warming and climate cycles on the environment in Kazakhstan annually for 40-45 years should be grown in large guantities and strongly photosynthe- tic long-lived woody plants, maple, arborvitae, oak, juniper,acacia and education of environmental patriotism.